CORONAVIRUS, ITS TYPES, BIOLOGICAL PROPERTIES, AND STRUCTURAL FEATURES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article presents historical data, general concepts, sources, transmission routes, types, biological properties, biochemical composition, receptors, pathogenesis of cell entry, morphogenesis, and pathomorphological changes in their invisible diseases.